Lightweight image encryption using integer reversible discrete Dual-Hahn transform on embedded systems - Mohamed Yamni; Achraf Daoui; Chakir El-Kasri; May Almousa; Ali Abdullah S. AlQahtani; Ahmed A. Abd El-Latif (Engineering Science and Technology, an International Journal, 2025)
The security and performance of a cryptographic algorithm can be reduced when implemented on an embedded system, such as a 32-bit microcontroller, due to the limitation of hardware resources, such as computational precision, processing power, and memory. This paper introduces the Integer Reversible Discrete Dual-Hahn Transform (IRDDHT), a novel integer-based transform designed for secure image encryption in resource-constrained embedded systems. The IRDDHT ensures lossless encryption by eliminating rounding errors common in floating-point transforms, maintaining image fidelity during encryption and decryption. We then propose a lightweight encryption algorithm based on IRDDHT, which introduces implicit diffusion and relies on parameter sensitivity to enhance security. When implemented on the ESP32 microcontroller, the proposed algorithm occupies less than 4 % of SRAM and 8.5 % of Flash memory, achieving a throughput of 170.67 kbps at the device’s maximum clock frequency. It is energy-efficient, capable of encrypting up to 129,025 grayscale images of size 256 × 256 pixels on a standard 3300 mAh battery. The algorithm ensures perfect decryption with no loss of image fidelity and demonstrates strong resistance to statistical attacks with near-ideal correlation values, as well as brute-force attacks with a large key space of 2199. These results indicate that the IRDDHT-based encryption method is an effective solution for secure image encryption in embedded systems.